ChemInform Abstract: Two‐Step Regioselective Synthesis of 3‐(Sulfonylamino)imidazo[1, 2‐a]pyrimidines from 2‐Aminopyrimidines and N‐(2, 2‐Dichloro‐2‐phenylethylidene)arensulfonamides. Issue 13 (March 2015) - Rozentsveig, Igor B.; Serykh, Valery Yu.; Chernysheva, Gulnur N.; Kondrashov, Evgeniy V.; Fedotova, Alena I.; Ushakov, Igor A.; Tretyakov, Evgeny V.; Romanenko, Galina V.
Abstract Reaction of various 2‐aminopyrimidines with imines (II) leads to addition of the ‐NH2 function to the azomethine group.